2017
DOI: 10.1016/j.aca.2017.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Sialic acid linkage-specific permethylation for improved profiling of protein glycosylation by MALDI-TOF MS

Abstract: Protein glycosylation mediates a wide range of cellular processes, affecting development and disease in mammals. Deciphering the “glycocodes” requires rapid, sensitive and in-depth characterization of diverse glycan structures derived from biological samples. In this study, we described a two-step derivatization strategy termed linkage-specific sialic acid permethylation (SSAP) consisting of dimethylamination and permethylation for the improved profiling of glycosylation by matrix-assisted laser desorption/ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 39 publications
(44 reference statements)
2
23
0
Order By: Relevance
“…For the distribution analysis of α2,3 or α2,6-sialylation ( Figure 5A ), only 71 distinct site-specific sialoglycopeptides contained pure α2,3-sialylation linkage, 186 sialoglycopeptides contained hybrid sialylation, and all the rest were uniquely 2,6-sialylated, which accounts for more than 77% of the identified sialoglycopeptides. This is consistent with the previous result that α2,6-sialylation is dominant in sialylated N-glycans released from human serum samples 54 . Taking a closer look at the distribution of sialylation levels, monosialylation is the major component in strictly α2,3 or α2,6-sialoglycopeptides, and 83% of the hybrid sialoglycopeptides are disialylated.…”
Section: Resultssupporting
confidence: 94%
“…For the distribution analysis of α2,3 or α2,6-sialylation ( Figure 5A ), only 71 distinct site-specific sialoglycopeptides contained pure α2,3-sialylation linkage, 186 sialoglycopeptides contained hybrid sialylation, and all the rest were uniquely 2,6-sialylated, which accounts for more than 77% of the identified sialoglycopeptides. This is consistent with the previous result that α2,6-sialylation is dominant in sialylated N-glycans released from human serum samples 54 . Taking a closer look at the distribution of sialylation levels, monosialylation is the major component in strictly α2,3 or α2,6-sialoglycopeptides, and 83% of the hybrid sialoglycopeptides are disialylated.…”
Section: Resultssupporting
confidence: 94%
“…On the other hand, structural features that will not directly yield a diagnostic ion can potentially be defined by incorporating additional chemo-enzymatic manipulation steps. For example, recent work by Jiang et el demonstrated that ␣2-3 and 2-6-sialic acids can be differentially derivatized by dimethylamidation followed by permethylation (25), resulting in 13 mass units difference between a methyl esterified and dimethyamidated sialic acid depending on whether it is 2-3 or 2-6-linked to Gal, respectively. This allows production of distinctive NeuAc ϩ and NeuAc-containing oxonium ions for a variety of ␣2-3/2-6-linked sialylated glycotopes to be distinguished and relatively quantified using our workflow.…”
Section: Discussionmentioning
confidence: 99%
“…However, the generated lactones suffer from the instability in water solution, resulting in poor reproducibility. In recent years, two‐step derivatization protocols have been applied to derivatize α2,3‐linked sialic acids to amides or esters instead of lactones . In the first step, α2,6‐linked sialic acids are efficiently derivatized by ammonium chloride, dimethylamine, or ethanol; whereas α2,3‐linked sialic acids form lactones.…”
Section: Oligosaccharidesmentioning
confidence: 99%
“…In recent years, two-step derivatization protocols have been applied to derivatize α2,3-linked sialic acids to amides or esters instead of lactones. [257][258][259][260][261] In the first step, α2,6-linked sialic acids are efficiently derivatized by ammonium chloride, dimethylamine, or ethanol; whereas α2,3-linked sialic acids form lactones. In the second step, the lactones are regenerated and subsequently converted to amides or esters.…”
Section: Amidationmentioning
confidence: 99%